Characteristics of The Patients with Low Back Pain in The Medical Rehabilitation Clinic, dr. Ramelan Naval Hospital Surabaya - Lena Wijayaningrum; Herin Setianingsih; Agustin Silfi Rahayu (Universitas Hang Tuah, 2019)
Background : The total number of visit of patients with low back pain in the Medical Rehabilitation Subdepartment of Dr. Ramelan Naval Hospital Surabaya from January to November 2018 is approximately 38.7% of all visits. Low back pain is defined as pain between the edge of the ribs and the gluteus fold which can be.Material and Methods : This was a cross sectional study, based on the analysis of the medical records from the LBP patients in July to September 2018, in the Dr. Ramelan Hospital RSAL Medical Rehabilitation Clinic. The inclusion criteria of LBP is: patient with main symptom of pain or other unpleasant feelings in the lower spine and surrounding areas, between the edge of the ribs and the gluteus fold. Results : There were 151 data analyzed from July to September 2018, patients with pain complaints were (86.84%). The data obtained showed majority of patients was 51-60 years old. Most of the patients were women.Conclusion : Most of the patients diagnosed with Low Back Pain (LBP) at the Medical Rehabilitation Clinic of RSAL Dr. Ramelan Surabaya, was 51-60 years old, women were the majority, 80%s had complain of pain and there were any of comorbidities.